Do E-Verify Mandates Improve Labor Market Outcomes of Low-Skilled Native and Legal Immigrant Workers? - Sarah Bohn; Magnus Lofstrom; Steven Raphael (Institute for the Study of Labor (IZA), 2015)
We examine the impact of state level legislation against the hiring of unauthorized immigrants on employment opportunities among competing low-skilled workers. Our focus is on the role of E-Verify mandates and specifically, we test for effects of the 2007 Legal Arizona Workers Act (LAWA) on employment outcomes of low-skilled native-born and legal immigrant workers in Arizona. We use the synthetic control method developed by Abadie, Diamond and Hainmueller (2010) to select a group of states against which the labor market trends of Arizona can be compared. Our results suggest that contrary to its intent, the Legal Arizona Workers Act does not appear to have improved labor market outcomes of competing legal low-skilled workers. In fact, we find some evidence of diminished employment and increased unemployment among legal low-skilled workers in Arizona. These findings are concentrated on the largest demographic group of workers – non-Hispanic white men. While they are less likely to find employment, those who do have on average higher earnings as a result of LAWA. The pattern of results points to both labor supply and labor demand contractions due to LAWA, with labor supply dominating in terms of magnitude.
Keywords: J8; J15; J18; J21; J31; J61; 330; illegal; unauthorized; undocumented; immigration; E-Verify; Arizona